Assessing the Tradecraft of Intelligence Analysis - Treverton, Gregory F. (RAND Corporation, 2008)
This report assesses intelligence analysis across the main U.S. intelligence agencies and makes a number of recommendations, some of which parallel initiatives that have begun in the wake of the December 2004 legislation, for instance, create a Deputy Director of National Intelligence as a focal point for analysis, establish a National Intelligence University, build a Long Term Analysis Unit at the National Intelligence Council, and form an Open Source Center for making more creative use of open-source materials.